Bio-based polymer networks by thiol-ene photopolymerization of allylated l-glutamic acids and l-tyrosines. (April 2018) - Aoyagi, Shima; Shimasaki, Toshiaki; Teramoto, Naozumi; Shibata, Mitsuhiro
Graphical abstract: Highlights: Tri- and tetra-allylated glutamic acids and tyrosines were prepared from glutamic acid and tyrosine. Thiol-ene photopolymerization of allylated amino acids gave flat films with smooth surfaces. The thiol-ene conversion increased by the thermal post curing. Thermal and mechanical properties were much improved by the thermal post curing. The cured products of allylated tyrosines exhibited the best thermal and mechanical properties. Abstract: Triallylated l -glutamic acid and l -tyrosine (A3E amd A3Y) and their tetraallyl derivatives (A4E and A4Y) were synthesized by reactions of l -glutamic acid and l -tyrosine with allyl bromide in the presence of potassium carbonate, respectively. Thiol-ene photopolymerizations of the allylated amino acids and a pentaerythritol-based tetrathiol (S4P) at allyl/SH 1/1 in the presence of photo-initiators produced photo-cured products (pA3E-S4P, pA3Y-S4P, pA4E-S4P and pA4Y-S4P). Furthermore, thermal post-curing after photo-curing of allylated amino acid/S4P mixtures containing photo-initiators and a thermal initiator produced photo and thermal cured products (ptA3E-S4P, ptA3Y-S4P, ptA4E-S4P and ptA4Y-S4P). Although the thermally post-cured products became dark in color, all the cured films were flat and had smooth surfaces. The FT-IR analysis revealed that allyl and thiol conversions increased by the thermal post-curing for all the curing systems. The glass transition temperature ( T g ), 5% weight loss temperature ( T d5 ), tensile strength and tensile modulus of each thermally post-cured product were higher than those of the corresponding photo-cured product, reflecting the increase of crosslinking density by the thermal post-curing. Also, A4E- and A4Y-based cured products exhibited higher T g s, T d5 s, tensile strengths and moduli than the corresponding A3E- and A3Y-based cured products, respectively. Especially, ptA4Y-S4P exhibited the highest T g (24.4 °C), T d5 (319 °C), tensile strength (18.2 MPa) and tensile modulus (1037 MPa) among all the cured products.